Vem är egentligen expert? : Hiphop som utbildningspolitik och progressiv pedagogik i USA - Söderman, Johan (Educare, 2011)
Who is the expert? Hip-hop as university politics and progressive education. Since hip-hop started over 35 years ago in New York, it has been associated with social activism and education. Accordingly, it is not surprising that academic institutions in universities and K-12 schools are interested in hip-hop with regards to the history of this street culture. This articles aim is to highlight this “hip-hop academization” and analyze the academization processes. The research questions are: How is hip-hop legitimized in official webpage texts? Who is the expert and what is at stake? What symbolic fights are going on between pioneers of the culture and academics? How do hip-hop scholars talk about the academization? The theoretical framework stems from sociologist Pierre Bourdieu, including his work within cultural fields and capital forms. The empirical data, which has been collected with an ethnographical approach, are webpage texts, observations, recordings from academic events concerned with hip-hop and individual interviews with hip-hop scholars in New York City during 2010. The results show how hip-hop at the university is an attractive label and a door-opener for the scholars, but at the same time how hip-hop is regarded as low-culture within the university. Finally, the data shows how the pioneers of hip hop construct the scholars as outsiders in order to maintain themselves as foremost experts of the culture.